The view from the other side of the fence: incarcerated women talk about themselves - Kuhlmann, Annette (2005)
Women are the demographic group with the fastest growing incarceration rates, yet historically women’s prisons have been built and organized according to the male model. In this manner female convicts’ special needs have been ignored. In recent years a small body of literature has begun to address the special situation of women in the criminal justice system, the way that the nature of their crimes and their life in prison is different than that of men and is rooted in patriarchy. Listening to the voices of the women themselves reveals the interrelated nature of the crimes for which they are convicted and their structural position.